Mating type of native Aspergillus flavus strains causing Corn Ear Rot in Argentina - Ruiz Posse, Agustina María; Torrico Ramallo, Ada Karina; Barontini, Javier Miguel; Camiletti, Boris Xavier (MDPI, 2025)
Fungi of the Aspergillus genus, particularly A. flavus, pose a significant threat to maize crops as they can produce toxic and carcinogenic aflatoxin compounds. This study focused on identifying the sexual mating types, MAT1-1 and MAT1-2, through PCR in A. flavus strains isolated from maize ears in two agricultural regions of Argentina—one subtropical and the other temperate—from the 2012/13 to the 2020/21 growing season. A total of 81 strains were analyzed, revealing a higher frequency of the MAT1-1 type in both regions (69%) and in the seasons with the highest number of strains collected. The MAT1-1 strains included 63% non-aflatoxigenic and 37% aflatoxin producers, predominantly lacking sclerotia production (69%), while MAT1-2 strains were mostly aflatoxin producers (82%) and S-sclerotia producers (48%). Additionally, more vegetative compatibility groups were identified as MAT1-1 (4 out of 6) than MAT1-2. These findings suggest that the use of MAT1-1 strains as biocontrol agents could maintain the stability of natural populations and reduce aflatoxin production, minimizing risks to crops. This underscores the importance of evaluating the genetic structure of A. flavus populations to implement effective biological control strategies.